2017
DOI: 10.20961/ijie.v1i2.11432
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Problem-Based Learning Model with Fishbone Diagram to Students's Critical Thinking Ability

Abstract: Abstract:Problem-based learning is characterized by the existence of a real problem as the context wherein students learn critical thinking skills, problem-solving, and knowledge acquisition. The concept of critical thinking gains popularity to help students obtain the ability to conduct fact analysis, support opinion with an argument, and problem-solving. The majority of Indonesian vocational school students, however, have difficulty in developing critical thinking skills and problem-solving. This research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
2
4
0
3
Order By: Relevance
“…The results showed that PBL had a superior effect compared to the DI model in achieving the CTA. The results of this study are in accordance with the results of previous studies (Celik et al, 2011;Istikomah et al, 2017;Jatmiko et al, 2018;Padmadewa&Ismoyo, 2017;Siew &Mapeala, 2016). The advantages of PBL compared to DI are due to the design of PBL models planned so that students have the ability to think critically, analytically, systematically and logically to determine alternative solutions to problems through exploration of empirical data to foster scientific attitudes (Santyasa, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that PBL had a superior effect compared to the DI model in achieving the CTA. The results of this study are in accordance with the results of previous studies (Celik et al, 2011;Istikomah et al, 2017;Jatmiko et al, 2018;Padmadewa&Ismoyo, 2017;Siew &Mapeala, 2016). The advantages of PBL compared to DI are due to the design of PBL models planned so that students have the ability to think critically, analytically, systematically and logically to determine alternative solutions to problems through exploration of empirical data to foster scientific attitudes (Santyasa, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…They actively build their knowledge and habit to think critically during PBL model (Yanto & Yerizon, 2018). It enables the, to survive when they face daily problems (Istikomah, Basori & Budiyanto, 2017).…”
Section: Pbl Model Effects On Critical Thinking Skillsmentioning
confidence: 99%
“…Science and Religion continue to bear the task of investigating coherently (neatly arranged ideas, facts, and ideas) become a logical sequence so that it is easy to understand the message they connect. Religion, if understood correctly, can confirm scientific exploration and strengthen our belief in the nature of reality that can continuously be understood (Istikomah et al, 2017).…”
Section: The Concept Of Integration Of Science and Learning Systemsmentioning
confidence: 77%